Um estudo de percepções de ONGs ambientalistas capixabas acerca da relevância de indicadores ambientais da GRI (Global Reporting Initiative) - Paris, Patrícia Krauss Serrano (2012)
The Global Reporting Initiative (GRI) stands out worldwide in order to minimize perceived quality problems in Sustainability Reports. One of GRI s initiatives is the development of environmental indicators. In the context of growing concern about environmental impacts of human activity, and considering environmental disclosure tool relevance for users depends on their relevance perception on the information it contains, the purpose of this study is: to analyze the perceived relevance by environmentalists non-governmental organizations (NGOs) in Espírito Santo (Brazilian state) on the essential environmental indicators in GRI s third version. Questionnaires were sent to 52 NGOs, resulting in 24 responses. Indicators and respondents were analyzed according to their responses profiles. It was found that all the environmental indicators considered essential by GRI were mostly indicated as being of significant importance, by respondents, what means GRI has the ability to meet this segment of Brazilian society s expectations. The results signalize the GRI essential environmental indicators importance on sustainability reports, and that disclosure standards internationalization for basic global issues related to the environment does not diminish its importance to users, in specific locations